Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1073/pnas.1012906108
|View full text |Cite
|
Sign up to set email alerts
|

DNA tandem repeat instability in the Escherichia coli chromosome is stimulated by mismatch repair at an adjacent CAG·CTG trinucleotide repeat

Abstract: Approximately half the human genome is composed of repetitive DNA sequences classified into microsatellites, minisatellites, tandem repeats, and dispersed repeats. These repetitive sequences have coevolved within the genome but little is known about their potential interactions. Trinucleotide repeats (TNRs) are a subclass of microsatellites that are implicated in human disease. Expansion of CAG·CTG TNRs is responsible for Huntington disease, myotonic dystrophy, and a number of spinocerebellar ataxias. In yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…Tandem-repeat instability varies as a function of the DNA sequence and the number of repeats (for example, CAG repeats are more instable than CTG repeats, and longer repeats are more instable [364]), their distance (365), their location in the genome (instability between repeats on the same molecules or on different molecules will result in different outcomes), and the cellular pathway leading to their instability (366). Additionally, the rate of tandem-repeat instability increases following DNA damage (367). Misalignment of repeated sequences might occur during DNA replication between the nascent strand and a second site on its template, on the nascent strand itself, or on the other sister chromosome.…”
Section: Genome Instability Due To Recombination At Repeated Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tandem-repeat instability varies as a function of the DNA sequence and the number of repeats (for example, CAG repeats are more instable than CTG repeats, and longer repeats are more instable [364]), their distance (365), their location in the genome (instability between repeats on the same molecules or on different molecules will result in different outcomes), and the cellular pathway leading to their instability (366). Additionally, the rate of tandem-repeat instability increases following DNA damage (367). Misalignment of repeated sequences might occur during DNA replication between the nascent strand and a second site on its template, on the nascent strand itself, or on the other sister chromosome.…”
Section: Genome Instability Due To Recombination At Repeated Sequencesmentioning
confidence: 99%
“…The rates of microsatellite instability can be modulated by different cellular processes using DNA synthesis, such as DNA replication, recombination, and repair. Furthermore, it has been shown recently that mismatch repair at these sequences can stimulate strand slippage at a longer directly repeated sequence located several kilobases away (367). Microsatellites occur naturally in numerous bacteria, and their expansions and contractions can regulate specific gene expression or alter coding sequences, resulting in phase or antigenic variation (see "Phase and Antigenic Variation in Bacteria," below).…”
Section: Genome Instability Due To Recombination At Repeated Sequencesmentioning
confidence: 99%
“…Blackwood and collaborators found that MMR at the site of an unstable trinucleotide repeat (TNR) array caused a stimulation of recombination at a nearby 275-bp tandem repeat. This stimulation occurred only when the tandem repeat was placed on the origin-proximal side the TNR that had generated a high frequency substrate for MMR (24). This Significance DNA mismatch repair (MMR) is critical to avoid mutations that can lead to genetic disease, cancer, and death.…”
mentioning
confidence: 99%
“…Length instability at the level of a single trinucleotide unit in a CTG·CAG repeat array that is inserted in the chromosome of E. coli is elevated in MMR deficient cells (24). This elevation of mutation occurs to an equal extent in mutS, mutL, and mutH mutants indicating that correction of the 3-base IDL, precursor to a single trinucleotide repeat unit change, occurs by a normal MMR reaction involving recognition by MutS and strand cleavage by MutH (24).…”
mentioning
confidence: 99%
See 1 more Smart Citation